DISTRIBUSI “WARISAN” MENGGUNAKAN MUFAKAT PERSPEKTIF MANAJEMEN KONFLIK: Studi di Masyarakat Desa Sedayu Kec. Turen Kab. Malang - Adhkar, Shohibul (UIN Sunan Kalijaga Yogyakarta, 2019)
Distribution of inheritance which is mean all the property of parents to all heirs, particularly children, it becomes an important part. Refer to the basic part of the inheritance law that has been written clearly in the Qur'an. But the fact in Sedayu Village Kec. Turen Kab. Malang which prefer to use consensus way or kinship deliberation. The aims of this study. First, to find out why Sedayu people uses consensus way in distributing inheritance. Second, To know the models of the distribution of inheritance in the community of Sedayu Village Kec. Turen. The method used in this research is Empirical Law or Social Law research with qualitative descriptive approach. While the data are extracted in the form of primary data derived from interviews and documentation of the informant, informant and respondent on the practitioner of inheritance distribution using consensus. To answer what are the fundamental reasons for consensus and how it is distributed. In this research, the researcher find the result of phenomenon data of the inheritance distribution that exist in the community of sedayu village. First, the fundamental reason they use consensus in the distribution of inheritance, to prevent conflicts when inheritance is distributed. Because for them the main family unity. The second reason with the consensus of the division of inheritance is more just and equitable without discrimination as in the inheritance of Islam. Secondly, the distribution model of the inheritance they use as well as the grant given to all the heirs in this case is the biological child, testament and inheritance they use are not in accordance with the Shari'a. Rather they equally share the heirs as in the grant. Based on the results of the research, it is concluded the reason for the village community using consensus in the division of inheritance is to overcome the conflicts which occurred during the division of inheritance, to keep the family together and with the consensus to be equally divided. The model used is not much different from the existing system in the Shari'a. But not in accordance with the Shari'a.